Reluctance and Its Role in Exemption of Criminal Liability (Salam International Academic Journal, 2014)
The principles of criminal penalties are created for the purpose of organizing criminal aspects and its penalties are of different and each of them has its own nature and its special objectives.  One of them is the principle of criminal liability. This principle is imposed on the criminal in order to determine the accountability of their transgressions committed under free will and wisdom, paving the way for bearing the punishment. Sometimes the perpetrator apparently commits a transgression, however he is exempted from the criminal liability and rules doesn’t apply. The barriers of criminal liabilities are the series of personal conditions under which the individual transgress and commits crime but he is exempted from the criminal liability. One the barriers is the compulsion or reluctance, under which the individual under some conditions is pushed to commit a crimes against his will. In our country, the principle of compulsion and reluctance comes under the general criminal law, within the barriers of criminal liabilities along with madness, emergency, age and intoxication. On the other hand, a newer debate that must be considered is placing the reluctance under the justified factors of crime. As this matter can bring a big change in the legal nature of reluctance, hence it requires a deep analysis. Although, this matter has not been under the consideration of lawyers; however according to Fiqh, in some cases, reluctance has been placed as justified factor of crimes. This research tries to study the placement of reluctance as justified factor of crime, while on the other hand, it tries to explore the laws of Afghanistan about reluctance
Keywords: Coercion; Criminal Responsibility; Compulsion; Danger; Threat